EFEKTIVITAS LAYANAN MOBILE JAMINAN KESEHATAN NASIONAL (JKN) DI PUSKESMAS PACET KABUPATEN MOJOKERTO - Safarah, Aidii; Fanida, Eva Hany (Publika, 2023)
The Mobile JKN application is one form of e-government implementation in healthcare services developed by BPJS and introduced to the public by CEO of BPJS, Fachmi Idris, in Jakarta on November 16, 2017. However, the application has not attracted many user, especially in the working area of Puskesmas Pacet, due to several problems such as lack of public knowledge about the use of the Mobile JKN application and difficulty accessing the application for those living in rural areas with poor signal reception. These problem have caused the public not to utilize the application properly, hampering administrative processes and delaying access to healthcare services. This study aims to describe the effectiveness of Mobile JKN services at Puskesmas Pacet in Mojokerto Regency. This research uses a quantitative descriptive method with data collection techniques of questionnaires, observation, and unstructured interviews. The research analysis is based on the E-Government Maturity Models theory explained in Permenpan RB Number 5 of 2018. The results show the effectiveness of Mobile JKN services at Puskesmas Pacet in Mojokerto Regency, such as the difficult signal reception in the rural working area, many patients only using the application for administrative purposes, frequent application errors, and many elderly patients not understanding how to use the application properly.